Vision impairment and food insecurity in the national health and aging trends study - Lee, Moon J.; Almidani, Louay; Samuel, Laura; Swenor, Bonnielin K.; Ehrlich, Joshua R.; Varadaraj, Varshini (Frontiers in Epidemiology, 2024)
Vision impairment (VI) may further exacerbate older adults' vulnerability to experiencing food insecurity and may be a unique and important target for policies addressing access to nutritional food.The purpose of this study is to determine the association of VI in older adults with food insecurity. This is a cross-sectional analysis of round 11 (2021) of the National Health and Aging Trends Study (NHATS), a nationally representative survey of U.S. Medicare beneficiaries age 65 and older.Participants include 2,815 older adults with complete data on at least one objective measure of vision (distance, near or contrast sensitivity) and food insecurity. Food insecurity was assessed using a previously developed indicator of food insecurity in NHATS. VI was defined as binocular visual acuity (VA) worse than 0.3 logMAR (Snellen equivalent 20/40) at distance or its near equivalent, or contrast sensitivity (CS) worse than 1.55 logUnits. Continuous VI measures included distance and near VA (per 0.1 logMAR), and CS (per 0.1 logCS). Participants were majority White (82%) and female (55%), and 3% had food insecurity. Older adults with any VI had a greater prevalence of food insecurity than adults without VI (5.0% vs. 2.0%, p<0.05). In fully adjusted regression analyses, individuals with any VI experienced double the odds of food insecurity than individuals without VI (OR: 2.1, 95% CI: 1.2-3.6). Distance VI (measured continuously) was associated with 1.2 times the odds of food insecurity (OR=1.2; 95% CI: 1.0-1.3, per 0.1 logMAR). All other vision measures trended towards higher odds of food insecurity, though not statistically significant. Older adults with VI experience higher rates of food insecurity than their peers. Interventions to improve food security should be targeted towards addressing the specific barriers faced by visually impaired older adults. Total Study Sample Any objective VI No objective VI Pvalu e Distance VI (<20/40) No Distance VI (≥ 20/40) Pvalu e Near VI (<20/40) No Near VI (≥ 20/40) Pvalu e CSI (<1.55 LogCS) No CSI (≥1.55 LogCS) Pvalu e Participants, n (%) 2,815 1075 (32) 1740 (68) 364 (10) 2,451 (90) 719 (21) 2,096 (79) (21) 2,113 (79)